Profiling Accounting Teachers’ Readiness for Online Learning During the Covid-19 Pandemic in the Eastern Cape in South Africa: Who Was Ready? - Skhepehe, Melikhaya (Research in Social Sciences and Technology- OpenED Network, 2024)
Regardless of the preparation of teachers, the COVID-19 pandemic and the ensuing social distancing measures forced educational institutions worldwide to convert quickly to online teaching and learning. COVID-19 has disrupted educational processes globally. The relevance of researching COVID-19's effects on the educational system has increased to discover a logical solution to this problem. This study assumes that a unit-level analysis can provide some insight, despite the pandemic's extensive consequences. Thus, during the Covid-19 outbreak in the Eastern Cape of South Africa, this study examined the preparation of accounting teachers for online learning. In a case study research design, a qualitative approach, a ten accounting teachers’ sample that was appropriate and intentional, was used. According to the survey, accounting learners are not aware of the potential applications of online learning in the classroom. The fact that schools do not promote online learning was another conclusion. The experts advise school administrators to schedule regular lectures online so that learners can learn. Redesigning classrooms is necessary to facilitate online learning.